Flowering and Fruiting Phenology of Rubus spp. in Cibodas Botanical Garden, Indonesia - Surya, Muhammad Imam; Rahman, Wiguna (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2012)
Flowering and fruiting phenology were studied in five species of Rubus spp (Rubus ellipticus, Rubus fraxinifolius, Rubus lineatus, Rubus moluccanus, and Rubus pyrifolius) which collected in Cibodas Botanical Garden. It has occurred since April 2009 to March 2010. Flowers and flower buds was produced every month by Rubus spp., but they produced difference amount. Furthermore, number of fruits was also shown a different in each species. This results show that each species has a different response to environment.